2007
DOI: 10.1021/cm702584d
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of Zoledronate with β-Tricalcium Phosphate for the Design of Potential Drug Device Combined Systems

Abstract: The reaction of aqueous Zoledronate solutions with β-tricalcium phosphate resulted in the precipitation of a crystalline Zoledronate complex on the surface of the calcium phosphate. This complex (CaNa[(HO)(C4H5N2)C(PO3)(PO3H)]·xH2O) was found to be metastable, leading to a pure calcium complex [Ca3[(HO)(C4H5N2)C(PO3)(PO3H)]2·xH2O] upon washing with water. This latter compound was found to release the bisphosphonate in phosphate buffers, in direct proportion to the phosphate concentration, while using a specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 63 publications
1
33
0
Order By: Relevance
“…Most commonly, the linkage of the drug to inorganic materials is made by soaking the inorganic scaffold in a BP solution, and recent examples of this method have been published in the last few years. 32,34,36,37,40,[132][133][134][135] In a relevant study, Boanini et al (2008) 132 synthesized HA nanocrystals loaded with different ALN contents (3.9, 6.2, 7.1 wt%). The in vitro evaluation showed that the presence of the BP in the composite nanocrystals produced a reduction in the number of osteoclasts of approximately 30% and an increase in osteoblastic growth and differentiation.…”
Section: Bte Using Bpsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most commonly, the linkage of the drug to inorganic materials is made by soaking the inorganic scaffold in a BP solution, and recent examples of this method have been published in the last few years. 32,34,36,37,40,[132][133][134][135] In a relevant study, Boanini et al (2008) 132 synthesized HA nanocrystals loaded with different ALN contents (3.9, 6.2, 7.1 wt%). The in vitro evaluation showed that the presence of the BP in the composite nanocrystals produced a reduction in the number of osteoclasts of approximately 30% and an increase in osteoblastic growth and differentiation.…”
Section: Bte Using Bpsmentioning
confidence: 99%
“…During the last decade, several studies that are related to the development of delivery systems for the controlled release of BP have been published. 7,29,[31][32][33][34][35][36][37][38][39][40][41] Smart methods of local drug delivery systems could increase the drug activity and specificity by concentrating the release of BP to bone sites and could reduce side effects at extra-skeletal sites. For those interested in further reading, a recent review summarizes the latest advances in the application of BPs for in situ orthopedic medication and treatments.…”
Section: Introductionmentioning
confidence: 99%
“…6 This similarity motivated the application of HAp as a synthetic biomaterial as has been evidenced in a large number of studies. [7][8][9][10][11][12][13][14][15] Furthermore, the formation of HAp can be regulated by DNA, which acts as a template in the process of "biomineralization". [16][17][18][19] This phenomenon is particularly important for biomedical applications requiring the protection of such biomolecules from aggressive environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Different types of CaP ceramics, such as hydroxyapatite (HA) [4], beta-tricalcium phosphate (β-TCP) [5], biphasic calcium phosphate (BCP) [6], amorphous calcium phosphate (ACP) [7] and calcium-deficient HA (CDHA) [8], have been studied as drug carriers in orthopaedic DDS applications. Among the different compositions of CaP materials, beta-tricalcium phosphate (β-TCP-Ca 3 (PO 4 ) 2 ) has attracted attention owing to its bioresorbability, which permits a gradual replacement of the implant by the newly formed bone [1,9].…”
Section: Introductionmentioning
confidence: 99%
“…In the mentioned examples [10][11][12][13][14], the feasibility of β-TCP as a potential drug carrier has been proved, its drug release behaviour in vitro and/or in vivo has been shown and the effect of parameters such as carrier porosity or chemical composition of β-TCP on drug delivery has been discussed. However, the type of interaction between the drug and the β-TCP drug carrier, which is an important factor in controlling drug release kinetics, has been highlighted in only a few studies [5,15].…”
Section: Introductionmentioning
confidence: 99%